Experimental and modeling studies on the enantio-separation of 3,5-dinitrobenzoyl-(R),(S)-leucine by continuous liquid–liquid extraction in a cascade of centrifugal contactor separators - Schuur, Boelo; Winkelman, Jozef G.M.; de Vries, Johannes G.; Heeres, Hero J. (Chemical engineering science, 2010)
The continuous enantioselective liquid–liquid extraction of aqueous 3,5-dinitrobenzoyl-(R),(S)-leucine (A R,S) using O-(1-t-butylcarbamoyl)-11-octadecylsulfinyl-10,11-dihydro-quinine (C, a cinchona alkaloid) as extractant in 1,2-dichloroethane (DCE) was studied experimentally in a countercurrently operated pilot scale cascade of six centrifugal contactor separators (CCS) at 294 K. The extractant was efficiently recovered by back-extraction in a single CCS allowing the cascade to be run continuously for 10 h. The steady-state ee of A R (ee R) in the raffinate was 42% at a 99% yield, the A S was obtained with high purity (98% ee S) and a yield of 55% in the back-extraction raffinate. In total 2.23 g of A S was obtained at steady-state operation from 8.11 g racemate feed. Deterioration of the ee in time was not observed, demonstrating the robustness of the chemistry. The experiments were modeled using an equilibrium stage approach. The correlation between model and experiment was satisfactory. The model was applied to optimize the production of both enantiomers in >97% ee. At zero reflux, 12 stages are required for 99% ee for both enantiomers. Application of a reflux allows a 25% reduction of the total liquid flow through the system by reduction of the wash feed as well as a reduction in the number of stages from 12 to 11. With a configuration of 12 CINC-V02’s operating at an aqueous feed flow of 360 mL/min, the model predicts that 17.7 kg racemate per week may be separated into both enantiomers with 99% ee using only 60 g of extractant.